Assessement of Sanitation and Health: A Case Study of Lower Bungongi, Northern Division Kabale Municipality - Daniel Nsenga (Uganda Christian University, 2025)
This research report was based on the study “to assess sanitation and health in lower Bungongi, Kabale Municipality.” The study was conducted following three objectives: the first one is to identify diseases or infections that are caused by poor sanitation; the second one is to propose proper waste management and water supply; and the third one is to investigate the strategies that can be adopted to reduce poor sanitation in lower Bungongi, Kabale Municipality. The researcher selected based on qualitative and quantitative research techniques and a sample size of eighty (80) respondents was used which consisted of a representative sample. The majority of the respondents 36 (45%) concurred that diarrheal diseases are sicknesses or infections which come as a consequence of poor sanitation in lower Bungongi, Kabale Municipality. Most of the respondents 45 (56.25%) consented that Waste Segregation and Recycling is a proper waste management and water supply method in lower Bungongi. 50 (62.5%) of the total respondents agreed that Community Engagement and Participation is one of the Strategies that can be adopted to reduce poor sanitation in lower Bungongi, Kabale Municipality. To sum up, the evaluation of sanitation and health in Uganda showcases a combination of advancement and ongoing issues. On the one hand, there have been great improvements in providing access to essential sanitation and health facilities, while on the other hand, inadequate sanitation, hygiene, and health care still exist for many Ugandans, especially in rural and marginalized areas. Based on the assessment of sanitation for enhancing the projection which include assigning enough funds for the construction, upkeep, and expansion of sanitation infrastructure like toilets, latrines,
Undergraduate